The Regulation Mechanisms and Clinical Application of MicroRNAs in Myocardial Infarction: A Review of the Recent 5 Years - Wu, Chan; Liu, Binghong; Wang, Ruiying; Li, Gang (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI) is the most frequent end-point of cardiovascular pathology, leading to higher mortality worldwide. Due to the particularity of the heart tissue, patients who experience ischemic infarction of the heart, still suffered irreversible damage to the heart even if the vascular reflow by treatment, and severe ones can lead to heart failure or even death. In recent years, several studies have shown that microRNAs (miRNAs), playing a regulatory role in damaged hearts, bring light for patients to alleviate MI. In this review, we summarized the effect of miRNAs on MI with some mechanisms, such as apoptosis, autophagy, proliferation, inflammatory; the regulation of miRNAs on cardiac structural changes after MI, including angiogenesis, myocardial remodeling, fibrosis; the application of miRNAs in stem cell therapy and clinical diagnosis; other non-coding RNAs related to miRNAs in MI during the past 5 years.